(untitled) (International Journal of Engineering and Computer Science, 2014)
Today the growth of cloud computing is riding a new role in corporate IT as a service broker. A hybrid cloud gives a choice to its customers in deploying the workload in a location with performance, security and utility is provided which remains a major concern for many IT organizations. When you decided to move to the cloud, one of your main ideas is probably to shift work from your hands or systems to someone else’s and to save money. In this scenario as work increases the cost of getting work done also increases. A hybrid cloud delivery model will operate as a broker of IT services, giving you more flexibility to best match your business’s needs and also provides you service on demand. The advantage of such a hybrid cloud deployment is that an organization only pays for extra compute resources when they are needed. We look into the architecture and reasons how Hybrid cloud are emerging as a better service brokers for business and customers